Giving Voice to African American Women’s Authentic Lived Experiences with Public Assistance - Adrienne C. Smith (Adult Education Research Conference, 2015)
African American women, welfare, and education and training are the focus of this research. Narrative Inquiry methodology was used to explore this qualitative study and it is grounded in the Africentric paradigm (Colin, III, 2010) utilizing the Womanist Epistemological Perspective (Sheared, 1994, 2010) for the unit of analysis. This study “gives voice” (Sheared 1994) to African American women authentic lived experiences (Colin, III, 2007) who have used the Temporary Assistance for Needy Families (TANF) program. Their stories highlight marginalization and oppression in access and utilization of the education and training activities in the temporary assistance program, capturing the women’s experiences from a polyrhythmic standpoint. In order for social welfare programs to be effective, women need personal development and quality adult education and training programs.
Keywords: African Americans; women; public assistance; womanist perspective